Mining Subsidence-Induced Microtopographic Effects Alter the Interaction of Soil Bacteria in the Sandy Pasture, China - Zhang, Qi; Ma, Jing; Yang, Yongjun; Luo, Zhanbin; Wang, Yifei; Chen, Fu (Frontiers in Environmental Science, 2021)
The microtopographic changes induced by coal mining subsidence caused a series of environmental problems such as soil erosion, and vegetation degradation in the mining area. However, the corresponding influence on surface vegetation and soil characteristic in different parts of the slope was completely different. To understand soil and vegetation degradation in coal mines and their future ecological restoration, it was crucial to investigate the origin. The relationship between soil microbial community diversity, structure, and taxa in the slope of subsidence area of different topographic locations in Daliuta coal mine, Shannxi, China, was determined by high throughput sequencing and molecular ecological network analysis. The relationship between the bacterial communities, environmental factors, and soil physicochemical properties was also investigated. We found a new topographic trait formed by surface subsidence to deteriorate the living environment of vegetation and the bacterial community. The vegetation coverage, soil water content, organic matter, and urease and dehydrogenase activities decreased significantly (p < 0.05). Although soil bacterial community diversity in the subsidence area did not differ significantly, the dominant taxa in different topographic locations varied. The molecular ecological networks representing bacterial community structure and function were also totally different. The networks in the middle and the top of the slope tend to be more complicated, and the interaction between species is obviously stronger than that of the bottom. However, the network in the bottom slope approached simplicity, and weak interaction, predominantly cooperative, was observed within and between modules. Meanwhile, the double stress of aridity and the lack of carbon source induced by subsidence also enhanced the capacity of the soil bacterial community to metabolize complex carbon sources at the bottom of the slope.